Efficient video hashing based on low‐rank frames. Issue 2 (4th October 2021) - Chen, Zhenhai; Tang, Zhenjun; Zhang, Xinpeng; Sun, Ronghai; Zhang, Xianquan
Abstract: Video hashing is a useful technology for diverse video applications, such as digital watermarking, copy detection and content authentication. This paper proposes a novel efficient video hashing based on low‐rank frames. A key contribution is the low‐rank frame calculation using the low‐rank approximation of singular value decomposition (SVD). As the large singular values of SVD are stable to digital operations, video hash extraction using low‐rank frames can provide good robustness. Since most energy is contained within the large singular values, low‐rank frames also contribute to discrimination. Moreover, two‐dimensional discrete wavelet transform (DWT) is applied to every low‐rank frame and the mean of low‐frequency DWT coefficients is selected as a hash element. Since these coefficients can represent input data approximately, hash discrimination is thus ensured. Experiments with 16, 850 videos are carried out to test performances of the proposed algorithm. The results show that the proposed algorithm outperforms some well‐known video hashing algorithms in computational time and classification about discrimination and robustness.